1998
DOI: 10.1115/1.2824335
|View full text |Cite
|
Sign up to set email alerts
|

Flow and Heat Transfer Characteristics Inside Packed and Fluidized Beds

Abstract: This paper investigates experimentally and theoretically the flow and heat transfer characteristics inside packed and fluidized beds. A single-blow transient technique combined with a thermal nonequilibrium two-equation model determined the heat transfer performances. Spherical particles were randomly packed in the test section for simulating the packed beds with porosity ε=0.38 and 0.39. Particles were strung with different spaces for fluidized beds with ε = 0.48 ~ 0.97. The ranges of dominant parameters are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 15 publications
0
21
0
2
Order By: Relevance
“…However, many other studies, which have examined systems far from thermal equilibrium, have reported breakthrough curves that are highly non-Fourier in nature (e.g., Liang and Yang 1975;Vafai et al 1985;Hwang and Chao 1994;Wu and Hwang 1998). Of these studies, we focus on the well-constrained data reported by Wu and Hwang (1998) for pseudo-1D experiments of forced convective flow through an artificial porous matrix.…”
Section: Comparison To Experimental Datamentioning
confidence: 96%
See 4 more Smart Citations
“…However, many other studies, which have examined systems far from thermal equilibrium, have reported breakthrough curves that are highly non-Fourier in nature (e.g., Liang and Yang 1975;Vafai et al 1985;Hwang and Chao 1994;Wu and Hwang 1998). Of these studies, we focus on the well-constrained data reported by Wu and Hwang (1998) for pseudo-1D experiments of forced convective flow through an artificial porous matrix.…”
Section: Comparison To Experimental Datamentioning
confidence: 96%
“…A step increase in temperature was applied to the inlet, and the evolution of temperatures at the outlet were subsequently Table 2. Experimental data from Wu and Hwang (1998) recorded. The highly non-Fourier behavior that was observed, which combined rapid thermal breakthrough with extremely long-tailing, was attributed to disequilibrium between the fluid and the porous matrix (Wu and Hwang 1998).…”
Section: Comparison To Experimental Datamentioning
confidence: 99%
See 3 more Smart Citations